2008
DOI: 10.2337/db07-1751
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of α4 Integrin Signaling Ameliorates the Metabolic Consequences of High-Fat Diet–Induced Obesity

Abstract: OBJECTIVE-Many prevalent diseases of advanced societies, such as obesity-induced type 2 diabetes, are linked to indolent mononuclear cell-dependent inflammation. We previously proposed that blockade of ␣4 integrin signaling can inhibit inflammation while limiting mechanism-based toxicities of loss of ␣4 function. Thus, we hypothesized that mice bearing an ␣4(Y991A) mutation, which blocks signaling, would be protected from development of high-fat diet-induced insulin resistance.RESEARCH DESIGN AND METHODS-Six-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 47 publications
3
28
0
2
Order By: Relevance
“…32, No. 7 similar effect [36]. In mice deficient for caveolin-1, a membrane-associated protein implicated in endothelial barrier function, rescue of caveolin-1 in endothelial cells reduces macrophage content in adipose tissue.…”
Section: Reviewmentioning
confidence: 78%
“…32, No. 7 similar effect [36]. In mice deficient for caveolin-1, a membrane-associated protein implicated in endothelial barrier function, rescue of caveolin-1 in endothelial cells reduces macrophage content in adipose tissue.…”
Section: Reviewmentioning
confidence: 78%
“…Although inhibiting α4 integrin function and signalling has been shown to block inflammatory responses associated with mononuclear cell-mediated diseases such as multiple sclerosis and Crohn’s disease [80,81], their role in low-grade chronic inflammatory conditions, such as obesity-induced insulin resistance is not well studied. However, it is shown that mice bearing an α4 (Y991A) mutation are protected from development of HFD-induced insulin resistance through mediating the trafficking of monocytes into adipose tissues [82]. …”
Section: Ecm Receptors In the Adipose Tissuementioning
confidence: 99%
“…14,77 In this context, it is of interest that mutation of the a4 chain of the a4b1integrin ligand for TF 14 in hematopoietic cells provides protection from adipose tissue inflammation, as seen with TF DCT mice. 78 In addition to their roles in macrophage recruitment, TF and PAR2 also regulate the activation of myeloid cells. 66,69 In microglia, lipopolysaccharide signaling in PAR2-expressing cells induces TNF-a and IL-6 production, whereas IL-10 is increased in PAR2-deficient cells.…”
Section: Cd11cmentioning
confidence: 99%